(3GdHQgGf aj CSQGQ Yde GdejRGfs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3bGd ai ChGFd cJGH GdfHGJ hCYde Cf GdUehZ efYbOI ef GdCdHGf s
(3BNQgG (B:s
(3Je GdefJNH ef cJGH GdfHGJ ef GdLRA GdQGHY ef GdHQgGf hChd eG fHOC HcJGH (B"(3GdCSQGH(B" (3bGd (B: (3aUd(B: s
(3Vef eLehY , JQJjHgG (B: (3ef U (B214 - (3U(B221s
(3GdehLhO efg efJNHGJ ef GdLRA GdQGHYs
(3GfXQ CjVkG GdeLehYI Qbe (B91s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs